Risky College Enrollment, Dropout, and Student Debt Forgiveness - Michael Kaganovich; Itzhak Zilcha (CESifo GmbH, 2025)
The paper analyzes the effects of two kinds of college education subsidies: unconditional tuition discounts and targeted forgiveness of student loans on student college enrollment and completion or dropout decisions. We focus on students' imperfect knowledge of their academic ability at the time of matriculation and its updating in the course of study as key factors in their responses to funding policies. We find that while unconditional tuition subsidies incentivize both matriculation and continued study even upon the revelation of low ability hence low returns to college, a policy combining such subsidy with partial forgiveness of student debt conditional on dropping out has a doubly efficient effect of risk mitigation: it maintains incentives to matriculate but discourages continued study when low future returns are revealed. It is, moreover, superior in terms of mitigating the "bad debt" held by students, that unrecouped by returns to college. Budget neutral conversion of a part of unconditional tuition subsidy to targeted debt forgiveness reduces the aggregate bad debt held by students.
Keywords: H52; I22; J24; 330; college enrolment; dropout; tuition subsidy; student debt